INFLUENCE OF PRODUCT PRICE AND SERVICE QUALITY ON THE INTEREST OF SHARIA RETAIL CONSUMERS - Rizki Annisa; Zulkarnain Lubis; Eka Ramdan Permana (El-Arbah: Jurnal Ekonomi, Bisnis Dan Perbankan Syariah, 2022)
TipTop is a modern retail business that is based on Islamic law both in terms of setting prices and services provided. With sharia principles, TipTop has succeeded in becoming the second ranked Top Brand for the last three years. This study aims to determine the effect of price and service quality on consumer interest in TipTop Pondok Bambu, using a quantitative approach and for this research sample was taken using the slovin formula with a sample of 100 consumers. The technique of collecting research data was collected using a questionnaire or questionnaire. With data analysis techniques Instrument Test (validity & Reliability), Classical Assumption Test (Normality, Multicollinearity & Heteroscedasticity) Model Test (Multiple Linear Regression, Coefficient of Determination (R2), Persian Correlation) Hypothesis Testing (T Test and F Test). Management of data in this study using software SPSS Version 16.0 for windows. From the results of data management the Classical Assumption test is normal, from the test results (T) the price has a sig value of 0.000 <0.05 which means it has a significant effect on consumer interest, from the test results (F) both have a significant effect simultaneously on consumer interest with the same value. sig of 0.000 <0.05 and from the results of the Coefficient of Determination Test the value of Rsquere is 0.688, which means that the price and quality of service have a strong relationship of 68.8% to consumer interest while the remaining 32.2 is influenced by other variables.